Heart failure medication and its effect on response to cardiac resynchronisation therapy in patients with pacing-induced cardiomyopathy: an UPGRADE post hoc analysis. (19th May 2022) - Barbieri, F; Spitaler, P; Adukauskaite, A; Rubatscher, A; Schgoer, W; Pfeifer, B; Hintringer, F; Dichtl, W
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): Austrian National Bank Unlimited scientific grant from the Boston Scientific Investigator Sponsored Research (ISR) Committee Background/Introduction: Current heart failure (HF) guidelines recommend optimal medical therapy (OMT) in patients with pacing-induced cardiomyopathy (PICM) prior upgrading to cardiac resynchronisation therapy (CRT). It is unknown, whether previous prescription of heart failure medication reduces the effect of CRT upgrading. Purpose: To evaluate the effect of HF medication on CRT response in patients suffering from PICM receiving an upgrade to CRT. Methods: The UPGRADE trial was a prospective investigator driven trial evaluating the effect of CRT upgrading in patients with PICM. Key inclusion criteria were symptomatic HF with left ventricular ejection fraction (LVEF) below 40% despite OMT and right ventricular pacing (RVP) above 40%. Device programming had to be adjusted to minimize RVP prior to enrolment. Echocardiographic examinations were performed prior to device implantation and 3-5 months after activation of CRT and were analyzed in blinded fashion. CRT response was defined by a reduction of > 15% in left ventricular end systolic volume (LVESV). Heart failure medication was assessed at implantation of the device. Results: Overall, 54 patients were enrolled in the UPGRADE trial between 2014 and 2018. Beta-blockers (BB) were prescribed in 43 (79.6%), mineralcorticoid receptor antagonists (MRA) in 29 (53.7%) and either an angiotensin-converting enzyme (ACE) inhibitor or an angiotensin II receptor blockers (ARB) in 45 (83.3%) of the patients. Therapy with CRT has led to significant improvement in LVEF (mean delta: 12.8 ± 7.8%) and LVESV (delta: 30.7 ± 33.2ml), whereas CRT response was achieved in 30 (55.6%) patients. There was no statistically significant difference in patients with BB intake regarding increase of LVEF (12.4 ± 7.5% vs. 14.6 ± 9.4%, p=0.431), decrease of LVESV (42.8 ± 32.8ml vs. 27.8 ± 33.0ml, p=0.201) or CRT response (22 (53.7%) vs. 8 (80%), p=0.167). Similar results were found regarding ACE inhibitor/ARB [LVEF: 13.1 ± 6.8% vs. 11.5 ± 11.8%, p=0.705; LVESV: 32.6 ± 32.6ml vs. 21.7 ± 36.3ml, p=0.373; CRT response: 26 (61.9%) vs. 4 (44.4%), p=0.460] and MRA intake [LVEF: 13.7 ± 7.3% vs. 11.8 ± 8.4%, p=0.382; LVESV: 34.3 ± 36.8ml vs. 26.7 ± 28.8ml, p=0.423; CRT response: 15 (55.6%) vs. 15 (62.5%), p=0.777]. Conclusion: Previous prescription of heart failure medication did not reduce the effect of CRT upgrading in patients suffering from PICM. It remains to be proven, whether similar results may be observed for newer HF agents like sodium-glucose co-transporter 2 inhibitors or angiotensin receptor-neprilysin inhibitors as both were not available in clinical routine at the time of study conduct.